ANALYSIS OF PRODUCTIVITY REPAIR BASED ON OEE VALUE ACHIEVEMENT OF SPEAKER SPARE PART PRODUCTION MACHINE IN WEST JAVA - Surya Perdana (Operations Excellence: Journal of Applied Industrial Engineering, 2018)
This research was conducted on companies engaged in the manufacture of Speakers, Megaphones and Amplifiers. The purpose of this study is: to determine the Overall Equipment Effectiveness (OEE) value of a machine so that steps can be taken to improve the effectiveness of the machine, in addition to knowing the main root causes of damage that often occur on the machine, and knowing how to solve the problem so that it can increase the productivity of the machine. In addressing this, an analysis of the performance of the machine is done by determining the identification based on the Overall Equipment Effectiveness (OEE) calculation ratio, namely availability time, downtime, machine working time, total output, operating time, cycle time and defect amount. Then calculate and analyze the OEE value: Availability Rate, Performance Rate, Quality Rate, Overall Equipment Effectiveness (OEE) and determine the value of Six Big Losses.The main causes of the low OEE value are the low Performance Rate with an average value of 75.01%, this is due to the value of Reduced Speed Losses which has the largest contribution in the six big losses.